Expanding Morning Report Beyond the Presentation: Using Morning Report Cases as a Tool for Resident and Faculty Education - Marc Yester; Michael Kidder (Association of American Medical Colleges, 2010)
Abstract At Wake Forest, our approach to Morning Report is similar to most institutions': A case is presented by an upper level resident, the patient is summarized, a differential diagnosis is explored, and the plan for further evaluation and management is discussed. Over the last 2 years, chief residents have worked to expand the educational opportunity that comes with each patient presented. Now, as cases are presented, we simultaneously create a document on the computer. Any photographs or radiographic images (deidentified) are added to the document. Next, we perform a literature and internet search of the topics discussed, with the goal of resident (and faculty) education in mind. A variety of resources may be included, depending on the particular case: review articles, recent primary research, landmark studies or historical articles, and/or presentations from our own faculty or those available online. Typically, we limit the number of resources per presentation four or less and include them in the document as hyperlinks. Our last addition to the document is the American Board of Pediatrics' Content Specifications to allow for board preparation. With this expansion of Morning Report, we now encompass at least four of the six ACGME Competencies: patient care, medical knowledge, practice-based learning and improvement, and interpersonal and communication skills. We have had an overwhelmingly positive response to the additions we have made to our Morning Report format. We now have increased faculty attendance, and faculty are more involved with case discussions. We are able to include many other residents and faculty who are unable to physically attend by publishing each case online for viewing at any time. Finally, although we do not have any objective evidence, we feel that learning based upon case presentations improves resident education. This daily exposure to real cases, along with the relevant literature and the ABP Content Specifications, offers an excellent opportunity for residents to work through a case, assess their own knowledge, and rectify any deficits with the provided resources. This resource is meant to serve as an example of how Morning Report can go beyond the traditional format to expand the learning opportunities. The materials needed include computer and projection equipment for the Morning Report presentation. Once the document is complete, all you need are website publishing software and a place to publish the website files. Our particular format requires 1-2 hours each day to complete the document. However, this time commitment could be shortened depending on the amount of resources added to the document. It is important to note that although we enjoy completing the document each day, it does require us to perform daily literature searches and to read the articles that we attach. We have found this daily task to be very enjoyable and educational, not burdensome.